FINANCIAL STATEMENTS OF ENTERPRISES AND THEIR IMPORTANCE - Kamola Mirhamidovna Tohirova (European Science Publishing, 2024)
The article provides recommendations on the importance of carrying out financial activities together with the main activities in enterprises, the correct organization of accounting for these activities based on international standards.
Keywords: financial activity, income of financial activity, expenses of financial activity, royalty, currency accounts.